Quality control of the breast ca treatments on HDR brachytherapy with TLD-100 (2023)
An anthropomorphic Phantom, a female trunk, was built with a natural bone structure and experimental material coated, glycerin and waterbased material called JJT to build soft tissue equivalent to the muscle of human tissue.